ANALYSIS OF CUSTOMER RELATIONSHIP MARKETING AT PT. BNI AMURANG - Pongoh, Stevani Agustin; Tielung, Maria V.J (Universitas Sam Ratulangi, 2018)
Abstract: Many companies are looking for ways to engage their customer to increase the interest, to build long-term relationship with customers. This the case in the development of the banking sector. This study analyzesnthe customer relationship marketing at PT. BNI Amurang. How BNIâ€™s implemented customer relationship marketing towards BNI performance. The objective of this study that is to find out the implementation of customer relationship marketing at PT. BNI Amurang. Theories that are used in this research are theories about customer relationship marketing and customer retention. This research used qualitative analysis, using the interview and observation techniques. The population of this research is all customers of BNI Amurang. And the sample is 10 respondents of BNIâ€™s customers and 2 staffs of BNI Amurang. The result from this research shows that customer relationship marketing at PT BNI Amurang have positive statement from 10 informants bonding with implementation of customer relationship marketing which is trust, commitment, communication, conflict handling. There are two recommendation in this research: first, customer relationship marketing are the action that the bank must consider to build positive and long-term relationship with customer. Second, the bank must improve how to deliver timely information to provide right information to customer.Â Keywords : customer relationship marketing, trust, commitment, communication, conflict handling.